Synthesis and Characterization of Fe@Cu Bimetallic Nanoparticle : Microemulsion Method (Journal of Nepal Physical Society, 2024)
The primary objective of this study is to synthesize Fe@Cu bimetallic nanoparticles (BNP’s) using the microemulsion technique. Microemulsion techniques are widely em- ployed for the controlled fabrication of nanoparticles with specific shapes and dimensions. The synthesized nanoparticles were characterized using UV-Vis spectroscopy, Fourier Transform Infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). X-ray diffrac- tion analysis revealed that the crystallite sizes of the Fe@Cu bimetallic nanoparticles fell within the range of 14.52 nm. The XRD graph also indicated the presence of copper peaks at (2θ) values of 34.52◦ , 42.60◦ , 50.60◦ , and 74.10◦ , as well as an iron peak at 43.70◦ . Ad- ditionally, we observed several oxide peaks for both copper and iron particles at 24.50◦ , 29.20◦ , 30.00◦ , 31.40◦ , 33.10◦ , 37.00◦ , and 61.80◦ , suggesting that a minor portion of copper had undergone oxidation and transformed into copper oxide. Peaks at 65.10◦ and 83.00◦ indicated the presence of iron oxide. UV-Vis spectroscopy of the Fe@Cu bimetallic nanoparticles exhibited a maximum peak at (312 ± 8.20) nm, with direct and indirect band gap energies of (2.54 ± 0.20) eV and (0.26 ± 0.02) eV, respectively. Both the indi- rect and direct band gaps demonstrated semiconductor behavior. Furthermore, UV-Vis spectroscopy revealed the surface plasmon resonance of Cu nanoparticles at (459 ± 1.13) nm. Fourier transform infrared spectroscopy of Fe@Cu bimetallic nanoparticles identified peaks at 680.87 cm−1 and 607.57 cm−1 , confirming the presence of Cu-O bonds, which align with Fe in the core and Cu on the shell. Moreover, this study included the prepa- ration of Cu@Fe bimetallic nanoparticles, as well as monometallic copper (Cu) and iron (Fe) nanoparticles. The characterization of these materials involved UV-Vis spectroscopy and FT-IR spectroscopy.